2019
DOI: 10.1523/jneurosci.0625-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Akt Phosphorylates NQO1 and Triggers its Degradation, Abolishing Its Antioxidative Activities in Parkinson's Disease

Abstract: The oxidative metabolism of dopamine and consequent oxidative stress are implicated in dopaminergic neuronal loss, mediating the pathogenesis of Parkinson's disease (PD). The inducible detoxifying antioxidative enzyme Quinone oxidoreductase (NQO1) (NAD(P)H: quinone oxidoreductase 1), neuroprotective to counteract reactive oxidative species, is most prominent in the active stage of the disease and virtually absent at the end stage of the disease. However, the molecular mechanism dictating NQO1 expression oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…Studies have shown that AKT also plays a role in PD signal transduction. As serine/threonine-specific protein kinases, AKT and phosphorylated AKT are significantly reduced in the substantia nigra pars compacta (SNpc) of PD patients [92]. PI3K/AKT/mTOR pathway activation also promotes the survival and growth of dopamine neurons by inhibiting apoptosis, thus preventing PD [93].…”
Section: Progress In Understanding the Role Of Pi3k/akt/mtor In Pdmentioning
confidence: 99%
“…Studies have shown that AKT also plays a role in PD signal transduction. As serine/threonine-specific protein kinases, AKT and phosphorylated AKT are significantly reduced in the substantia nigra pars compacta (SNpc) of PD patients [92]. PI3K/AKT/mTOR pathway activation also promotes the survival and growth of dopamine neurons by inhibiting apoptosis, thus preventing PD [93].…”
Section: Progress In Understanding the Role Of Pi3k/akt/mtor In Pdmentioning
confidence: 99%
“…Oxidative phosphorylation is a vital part of metabolism, takes place in the mitochondria, and contributes to the major source of ATP. This process also leads to the generation of reactive oxygen species (ROS) and resulting oxidative stress and bioenergetics defects, which are linked to a range of neurodegenerative disorders, including PD [37][38][39]. While oxidative stress has been shown to play significant roles both in the onset and progression of PD [40], it still remains open to debate whether the mitochondrial respiratory deficiencies observed in a range of neurodegenerative disorders are initiators or consequences of prior insult [41].…”
Section: Discussionmentioning
confidence: 99%
“…The Pro187Ser variant decreases NQO1 activity due to a large defect in FAD binding (10- to 40-fold lower affinity than that of WT) and in conformational stability, leading to its rapid intracellular degradation by the proteasome [1,10,14,16,22,23,24,25]. In general, reduced NQO1 activity or protein levels are commonly observed under these pathological conditions [1,26], although for the particular case of cancer, overexpression of NQO1 is also associated with cancer progression, which makes pharmacological inhibition of NQO1 (e.g., by dicoumarol or related compounds) a potential therapeutic strategy to treat this disease if it selectively targets cancer cells [27,28,29]. Linked to some of these pathological conditions, the intracellular stability of NQO1 WT is controlled by the population of the NQO1 apo state, which is efficiently targeted to the ubiquitin-dependent proteasomal degradation pathway [14,25,30].…”
Section: Introductionmentioning
confidence: 99%